2020
DOI: 10.1088/1748-605x/aba326
|View full text |Cite
|
Sign up to set email alerts
|

Does the Inion OTPSTM absorbable plating system induce higher foreign-body reaction than titanium implants? An experimental randomized comparative study in rabbits

Abstract: Hardware removal after complete fracture healing is a laborious and traumatic procedure that bears the risks of refracture, infection, and soft tissue damage. Absorbable materials for fracture fixation have the advantage of eliminating the need for removal; however, they may stimulate a considerable inflammatory response. For that reason, we compared in a prospective randomized experimental animal model study the incidence of foreign-body reactions between Inion OTPSTM absorbable plate implants, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…There have been numerous in vivo studies characterizing the host immune cellular response to polylactide (PLA). While being highly informative, the complexity of the in vivo microenvironment where PLA is implanted could preclude a thorough understanding of mechanistic events therein. To deconvolute in vivo events, several in vitro studies have been undertaken. However, many prior in vitro models on PLA biocompatibility focused on acidity, based on prior correlation between reduced pH and the adverse immune responses elicited by PLA. , Instead, this study builds on observed alterations in bioenergetics as well as metabolic reprogramming as drivers of adverse immune responses to polyethylene wear particles , after total joint replacements and PLA biomaterials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous in vivo studies characterizing the host immune cellular response to polylactide (PLA). While being highly informative, the complexity of the in vivo microenvironment where PLA is implanted could preclude a thorough understanding of mechanistic events therein. To deconvolute in vivo events, several in vitro studies have been undertaken. However, many prior in vitro models on PLA biocompatibility focused on acidity, based on prior correlation between reduced pH and the adverse immune responses elicited by PLA. , Instead, this study builds on observed alterations in bioenergetics as well as metabolic reprogramming as drivers of adverse immune responses to polyethylene wear particles , after total joint replacements and PLA biomaterials .…”
Section: Discussionmentioning
confidence: 99%
“…While different immune outcomes occur following surgical implantation of various types of PLA, this observation has not been previously modeled in vitro. Not only do we model this phenomenon, but we also reveal the biological mechanisms that explain the complex relationships among material stereochemistry, immune responses, bioenergetics, and metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…However, after surgical implantation, PLA elicits adverse immune responses in up to 44% of human patients, often requiring further interventions 2,3 . In animals, a 66% incidence of excessive fibrosis with capsules from long-term inflammation which significantly limit implant-tissue integration has been reported 4 . PLA degrades by hydrolysis into D- or L-lactic acid, with semi-crystalline PLA degrading slower and tending to contain less D-content than amorphous PLA 1,5 .…”
mentioning
confidence: 99%
“…In this specific case there were no clinical (or systemic) signs of infection. However the ESR was slightly increased this can be seen in any inflammatory process, for example a foreign body reaction [ 8 ]. Whenever there would be an acute infection one would expect increased leukocytes, lowered Hb and increased ALAT.…”
Section: Discussionmentioning
confidence: 99%